2011
DOI: 10.1111/j.1469-7610.2010.02352.x
|View full text |Cite
|
Sign up to set email alerts
|

ERPs associated with monitoring and evaluation of monetary reward and punishment in children with ADHD

Abstract: The lack of modulation of the FRN by contingencies in ADHD suggests deficient detection of environmental cues as a function of their motivational significance. LPP findings suggest diminished response to punishment, but oversensitivity to the loss of desired rewards. These findings suggest that children with ADHD have problems assigning relative motivational significance to outcomes of their actions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
44
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 53 publications
11
44
1
Order By: Relevance
“…when the choice was unrewarded) in both groups (intact versus lesioned model, (t(19)=14.21, p<0.0001). Again the RVPM activation is consistent with experimental data from ADHD patients, who exhibit a reduced amplitude of error related activity in EEG studies (Groen, et al, 2008;Herrmann, et al, 2010;van Meel, et al, 2011), if we 13 assume error-related activity to be due to reward omission (Holroyd & Coles, 2002).…”
Section: Simulation 1: Probabilistic Choice Taskssupporting
confidence: 83%
See 1 more Smart Citation
“…when the choice was unrewarded) in both groups (intact versus lesioned model, (t(19)=14.21, p<0.0001). Again the RVPM activation is consistent with experimental data from ADHD patients, who exhibit a reduced amplitude of error related activity in EEG studies (Groen, et al, 2008;Herrmann, et al, 2010;van Meel, et al, 2011), if we 13 assume error-related activity to be due to reward omission (Holroyd & Coles, 2002).…”
Section: Simulation 1: Probabilistic Choice Taskssupporting
confidence: 83%
“…The latter characteristic is possibily related mainly to the hyperactive/impulsive dimension of ADHD , which could explain why some studies reported null results. Altered reinforcer sensitivity is reflected in altered electrophysiological activity related to RL processing (Groen, et al, 2008;Herrmann, et al, 2010;van Meel, Heslenfeld, Oosterlaan, Luman, & Sergeant, 2011;van Meel, Oosterlaan, Heslenfeld, & Sergeant, 2005).…”
Section: Rl Impairment In Adhdmentioning
confidence: 99%
“…Holroyd et al (2008) reported that children with AD/HDcom showed an atypical time-on-task effect in a virtual maze guessing task, with larger feedback ERN amplitude in the second than first half of the task, due mainly to a physical monetary reward at the half-way point and subsequent increased task engagement. In a time estimation task with visual feedback, children with AD/HDcom did not show differential modulation of FRN in reward and punishment conditions, or late positive potential (LPP) enhancement to punishment, indicating less effective monitoring of feedback and subsequent insufficient attention to feedback (van Meel et al, 2011).…”
Section: Feedback Processingmentioning
confidence: 91%
“…These processes play a role in monitoring or evaluation, and are differentially activated when an outcome is unexpected, incorrect, unfavourable, or in conflict with goals (van Meel et al, 2011).…”
Section: Performance Monitoringmentioning
confidence: 99%
See 1 more Smart Citation